Telenursing Education Based on Health Belief Model Improves Self-Care for Hypertension Patients - Emdat Suprayitno; Ratna Indriyani; Mujib Hannan; Syaifurrahman Hidayat; Suraying Suraying (GLOBAL HEALTH SCIENCE GROUP, 2024)
Non-communicable diseases (NCDs) are prevalent in society, especially in Indonesia, including hypertension. The emergence of health problems here is caused by individual negligence, such as unhealthy eating patterns and can also be caused by public ignorance about maintaining health. The purpose of this study was to determine the effect of telenursing education on self-care management in hypertension patients in the Manding Health Center work area. The research method used in this study uses quantitative research using design Quasi Experimental, with control group (pretest-posttest with control group design). The sampling method used in this study was simple random sampling. Data collection used a questionnaire with the Borg Scale and Leiceste Cugh Questionnaire instruments. This study began with a pretest then provided telenursing self-care management education once a week for one month in the treatment group and continued with a posttest. The results of this study indicate that there is an influence before and after being given telenursing education on the treatment group. Based on the Wilcoxon test in the treatment group before and after being given education, p = 0.000 (p <α) was obtained, which means that there is an influence of Telenursing Self Care Management Education on Self Care Management in hypertension patients. Seeing the results of this study, it is recommended for hypertension sufferers to pay more attention to their health and carry out all components of hypertension control in a disciplined manner.